Profitability and Constraints of Median Scale Battery Cage System of Poultry Egg Production in Edo State, Nigeria - Ekunwe, P.A.; Soniregun, O.O. (International Journal of Poultry Science, 2007)
This research was aimed at examining the Profitability and Constraints of medium scale Battery Cage system of Poultry farmers involved in egg production in Edo State. Nigeria. A total of 100 questionnaires were administered and the simple random sampling technique was used to select egg producers from Oredo Local Government Area (LGA) of Edo State of which eighty eight questionnaires were found suitable for analysis. Descriptive statistics such as tables, frequency distribution and percentages were used to determine the socio-economic characteristics of the poultry farmers. The gross margin analysis, net returns and return per naira were used to determine the profitability of egg production. The constraints to egg production were analyzed using the likert scale technique. The results of the analysis revealed that the average number of birds raised is 1,930 birds. (This revealed that the system was operated under small-Scale). The study revealed that 44% and 54% of the respondent was females and males respectively. The results of the study also revealed that the fixed capital investment per farm was N 474, 988.65. Also, total fixed cost less depreciation was N 423,545.86. The study also revealed that total revenue and net returns from the sales of egg and other sources per bird per year was N3, 421.86 and N3, 168.70 respectively. Finally the major constraints faced by the farmers are in the order of inadequate finance, high cost of feed, low egg price and high cost of medicine and vaccine.